1998
DOI: 10.1039/a804940h
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled synthesis and reactivity of sugar acetylenes

Abstract: C-Glycosidation is of great significance in the organic synthesis of optically active materials, since it allows the introduction of carbon chains to sugar chirons and the use of sugar nuclei as a chiral pool as well as a carbon source. Silylacetylenes are sufficiently reactive to form 'sugar acetylenes' for the selective introduction of various acetylenic groups in an alpha-axial manner at the anomeric position of D-hexopyranose rings. 1,4-Anti induction, on the other hand, gives a different stereochemical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Those alkynylated compounds are called "sugar acetylenes" [45]. The mechanism includes eliminative formation of cation to which silylacetylene can coordinate on the α-face (Scheme 40).…”
Section: Silyl-based Nucleophilesmentioning
confidence: 99%
“…Those alkynylated compounds are called "sugar acetylenes" [45]. The mechanism includes eliminative formation of cation to which silylacetylene can coordinate on the α-face (Scheme 40).…”
Section: Silyl-based Nucleophilesmentioning
confidence: 99%
“…Herein we describe an efficient stereocontrolled synthesis of a-C-mannosyltryptophan (2). 13 In our previous paper, a dehydrotryptophan intermediate was synthesized from C-mannosylindole 3, which was prepared from D-mannose derivative 5 through ethynylmannose 4 by stereoselective a-C-glycosidation 14 with tinacetylene and Castro indole synthesis as the key steps (Scheme 1). 15 However, hydrogenation of the dehydrotryptophan gave a diastereomeric mixture, whose absolute stereochemistry has not been determined.…”
mentioning
confidence: 99%
“…[20][21][22] acetate, which was treated with a large amount of NaBH 4 in the presence of CeCl 3 to afford allylic alcohol 22 in 53% overall yield from 20. In the next epoxidation with MCPBA, we found that bis-TBS ether 23 derived from 22 was the best substrate to obtain high yield of -epoxide 24.…”
Section: Resultsmentioning
confidence: 99%